FUNGSI DAN MAKNA SIMBOLIK TINGKULUAK KOTO NAN GADANG PAYAKUMBUH - Imelda, Desra (Studi Budaya Nusantara, 2020)
Koto Nan Gadang is one of the nagari in North Payakumbuh that still preserves Minangkabau traditional clothes, this can be seen when carrying out traditional ceremonies such as weddings, batagak pengulu, and others. The community still respects the local cultural customs by still wearing traditional clothing during the event process. This research is about Tingkuluak Koto Nan Gadang which is devoted to the function and meaning of the symbols contained in each tingkuluak. It was concluded that Tingkuluak Koto Nan Gadang has several functions, namely as mamanggia traditional clothes, clothes for maanta, and clothes to await guests. Tingkuluak Koto Nan Gadang is also a symbol and sign for the wearer, others will be able to know the status of the wearer from the clothes he wears.